Spectroscopic and Computational Studies on the Adenosylcobalamin-Dependent Methylmalonyl-CoA Mutase: Evaluation of Enzymatic Contributions to Co−C Bond Activation in the Co3+ Ground State - Brooks, Amanda J; Vlasie, Monica; Banerjee, Ruma; Brunold, Thomas C (Journal of the American Chemical Society, 2004)
Methylmalonyl-CoA mutase (MMCM) is an enzyme that utilizes the adenosylcobalamin (AdoCbl) cofactor to catalyze the rearrangement of methylmalonyl-CoA to succinyl-CoA. Despite many years of dedicated research, the mechanism by which MMCM and related AdoCbl-dependent enzymes accelerate the rate for homolytic cleavage of the cofactor's Co−C bond by ∼12 orders of magnitude while avoiding potentially harmful side reactions remains one of the greatest subjects of debate among B12 researchers. In this study, we have employed electronic absorption (Abs) and magnetic circular dichroism (MCD) spectroscopic techniques to probe cofactor/enzyme active site interactions in the Co3+Cbl “ground” state for MMCM reconstituted with both the native cofactor AdoCbl and its derivative methylcobalamin (MeCbl). In both cases, Abs and MCD spectra of the free and enzyme-bound cofactor are very similar, indicating that replacement of the intramolecular base 5,6-dimethylbenzimidazole (DMB) by a histidine residue from the enzyme active site has insignificant effects on the cofactor's electronic properties. Likewise, spectral perturbations associated with substrate (analogue) binding to holo-MMCM are minor, arguing against substrate-induced enzymatic Co−C bond activation. As compared to the AdoCbl data, however, Abs and MCD spectral changes for the sterically less constrained MeCbl cofactor upon binding to MMCM and treatment of holoenzyme with substrate (analogues) are much more substantial. Analysis of these changes within the framework of time-dependent density functional theory calculations provides uniquely detailed insight into the structural distortions imposed on the cofactor as the enzyme progresses through the reaction cycle. Together, our results indicate that, although the enzyme may serve to activate the cofactor in its Co3+Cbl ground state to a small degree, the dominant contribution to the enzymatic Co−C bond activation presumably comes through stabilization of the Co2+Cbl/Ado• post-homolysis products.